ANALISIS BUTIR SOAL ULANGAN HARIAN KEMAGNETAN DAN INDUKSI ELEKTROMAGNETIK KELAS IX SMP - Lia Triani; Reni Marlina; Semuel Riak (Academy of Education Journal, 2023)
This study aims to determine the quality of the questions used in the daily tests on magnetism and electromagnetic induction for class IX in junior high school. The number of questions analyzed was 10 multiple-choice questions and 5 essay questions. The analysis technique for the quality of the items was carried out through a quantitative descriptive approach with the criteria for the quality of the questions which included validity, reliability, item discrimination, and the degree of difficulty of the questions which were carried out on 108 students. Through the results of calculations and analysis, data is obtained that all questions are valid and have high reliability, with a PG reliability value of 0.64 and essay reliability of 0.65. The results of the analysis of the degree of difficulty of the 15 PG questions and essays were that there were 3 questions (20%) in the easy category, 11 questions (73.3%) in the moderate category, and 1 item (6.7%) in the difficult category. The discriminating power analysis of 15 PG questions and essays obtained 4 very good questions (26.7%), 7 good questions (46.7%), 3 fairly good questions (20%), and 1 poor question (6.6%).